Intermediatfilamente im Cytoskelett und Struktur der Wolle - Helmut Zahn (CHIMIA)
«From the hairs on our head to the soles of our feet, our bodies are composed of cells rich in intracellular fibrous proteins called intermediate filaments (IF): a complex group of 30 or so keratins of 40-70 kd in epithelia; a single protein desmin of 52 kd in muscle; a single protein vimentin of 53 kd in cells of mesenchymal origin; glial fibrillary acidic protein (GFAP), a single protein of 50 kd in astroglia; and a triplet of neurofilament proteins, NF-L, NF-M, NF-H in neuronal cells». This introduction to the review «The Molecular Biology of Intermediate Filaments» written 1985 by Steinert et al.[1a], starts with the hairs on our head, but hair and sheep wool, so-called «hard keratins», were only recently accepted as full members of the IF-family, although decisive criteria for the membership such as diameter of the filaments (7-11 nm), supercoiled α-helical structure, and molecular weight of the proteins subunits have been fulfilled by wool and other keratin fibres. When α-keratins were finally recognized by sequence comparison as intermediate filaments in 1982 by Geisler and Weber[2a] the lack of reconstitution of isolated microfibrillar proteins from wool in filaments in vitro posed a special problem as all other proteins of this family readily form filaments. By adopting a new procedure for preparing wool proteins and hair proteins without carboxymethyl groups, it was possible to achieve polymerization in vitro in dilute solutions into filaments that have the same structure as the in situ keratin filaments in wool and hair. These results open the way for a more sophisticated analysis of the chemical quality of wool and hair by assessing the yield and geometry of reconstituted filaments.